Career Guidance Helps Students Choose the Right Career Path - Yulianti Yulianti; Syakila Finanjani; Dwi kurnia Sari; Asmawati Asmawati (Universitas Muhammadiyah Enrekang, 2023)
Currently, many students still choose majors that do not align with their actual career aspirations. Career guidance plays a crucial role in helping students identify their interests, talents, values, and life goals. Therefore, career guidance is a process of guidance and support, aiding students in making more confident and informed decisions. Additionally, career guidance is a vital aspect of education aimed at assisting students in developing self-awareness and selecting suitable career paths. Through a profound understanding of students' interests and potentials, career guidance can assist them in navigating a more purposeful career path selection process while minimizing the risk of making decisions that do not align with their desires and talents. The methodology employed involves the analysis of various literature sources, journals, and articles relevant to the topic. The analysis highlights that career guidance is not only about choosing a job but also about laying a strong foundation for a successful and fulfilling future.